Interaction of the isolated domain II/III of Thermus thermophilus elongation factor Tu with the nucleotide exchange factor EF-Ts. - Peter, M E (Nucleic Acids Res, 1990)
The middle and C-terminal domain (domain II/III) of elongation factor Tu from Thermus thermophilus lacking the GTP/GDP binding domain have been prepared by treating nucleotide-free protein with Staphylococcus aureus V8 protease. The isolated domain II/III of EF-Tu has a compact structure and high resistance against tryptic treatment and thermal denaturation. As demonstrated by circular dichroism spectroscopy, the isolated domain II/III does not contain any alpha-helical structure. Nucleotide exchange factor, EF-Ts, was found to interact with domain II/III, whereas the binding of aminoacyl-tRNA, GDP and GTP to this EF-Tu fragment could not be detected. IMAGES: